Iron-Catalyzed Aerobic Oxidative Cross-Dehydrogenative C(sp3)–H/X–H (X = C, N, S) Coupling Reactions - Hu, Ren-Ming; Lai, Yi-Huan; Xu, Da-Zhen (Synlett, 2020)
The direct functionalization of C(sp3)–H bonds is an attractive research topic in organic synthetic chemistry. The cross-dehydrogenative coupling (CDC) reaction provides a simple and powerful tool for the construction of C–C and C–heteroatom bonds. Recently, some progress has been made in the iron-catalyzed aerobic oxidative CDC reactions. Here, we present recent developments in the direct functionalization of C(sp3)–H bonds catalyzed by simple iron salts with molecular oxygen as the terminal oxidant.1 Introduction2 C(sp3)–C Bond Formation3 C(sp3)–N Bond Formation4 C(sp3)–S(Se) Bond Formation5 Conclusion and Outlook
Keywords: iron; cross-coupling reaction; aerobic oxidative reaction; green synthesis; synthetic methods